Training process modeling of hammer throwers taking into account peculiarities of stress adaptation - Bolotin, A.; Bakayev, V. (Proceedings of the 6th International Conference on Sport Sciences Research and Technology Support - Volume 1: icSPORTS, 2018)
The article considers the solution of the forecast problem to improve the efficiency of the training process of hammer throwers taking into account the peculiarities of their adaptation to the load. This problem was solved by computer modelling. To solve this problem, restrictions were set on the control and managed parameters. The number of parameters that were entered into the model was determined by the methods of expert assessments. These parameters were adjusted in the process of modelling the dynamics of the training system in time on a personal computer. Basing on the results of forecasting it was revealed that taking account the peculiarities of stress adaptation in hammer throwers training led to doubled number of sportsmen`s who fulfilled the qualification norm successfully.